2022
DOI: 10.23918/ijsses.v9i1p269
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing EFL Learners’ Vocabulary Acquisition with Socrative Digital Flashcards: An Experimental Study

Abstract: Effective communication in a foreign language requires an in-depth knowledge of the language's vocabulary. Teachers are expected to include interactive multimedia in their vocabulary instruction. The current study examined the impact of Socrative digital flashcards on English as a foreign language (EFL) learners' vocabulary acquisition. The study recruited 54 students from the State Junior High School of Malang in Indonesia. Their ages varied from 12-14 years old. This was a quasi-experimental study, and they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…The study by Rahmawati and Liskinasih (2022) aims to determine how Socrative digital flashcards affected the students' vocabulary acquisition. The findings revealed that students who used Socrative had significantly higher vocabulary acquisition than groups who used PowerPoint flashcards.…”
Section: Usage Of Flash Cardmentioning
confidence: 99%
“…The study by Rahmawati and Liskinasih (2022) aims to determine how Socrative digital flashcards affected the students' vocabulary acquisition. The findings revealed that students who used Socrative had significantly higher vocabulary acquisition than groups who used PowerPoint flashcards.…”
Section: Usage Of Flash Cardmentioning
confidence: 99%